From Stool to Statistics: Reporting of Acute Gastrointestinal Illnesses in Canada - Flint, James A. (Can J Public Health, 2004)
Background: Limitations associated with the under-reporting of enteric illnesses have long been recognized but the extent and variation of this under-reporting in Canada has not been examined. Given the public health value of surveillance data, a closer examination of under-reporting of enteric illnesses in Canada was warranted. Methods: Paper-based surveys were administered (a) to all laboratories in Canada licensed to process stool specimens and (b) to all local public health authorities in two provinces. Results: Of the laboratories surveyed, 67% (n=274) conducted on-site testing of stool specimens for enteric bacteria, 31% (n=126) for parasites and 10% (n=42) for viruses. In the year 2000, these laboratories processed 459,982 stool specimens, of which 5%, 15%, 8% and 19% were positive for enteric bacteria (excluding C. difficile), C. difficile, parasites and viruses, respectively. Variations in laboratory testing and health authority reporting protocols and policies were identified. Of the laboratory-confirmed cases of AGI reported to local public health authorities, 5% (n=846) were not reported to provincial counterparts. Conclusion: A significant proportion of AGI cases submitting stool specimens are not captured in Canada’s passive surveillance system due to unknown etiology. A much smaller proportion of laboratory-confirmed cases reported to local public health authorities are not captured at the provincial or national level. Given that the number of laboratory-confirmed AGI cases represents such a small fraction of all community cases, strategies to compensate for under-reporting and efforts directed at harmonizing laboratory and local public health authority policies and practices would be welcomed.